2013
DOI: 10.1007/s10725-013-9821-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and differential expression of protopanaxadiol synthase in Asian and American ginseng ginsenoside biosynthesis by RNA interferences

Abstract: Asian ginseng (Panax ginseng) and American ginseng (Panax quinquefolium), are thought to be representative plant of Panax species, have important commercial value and are used in worldwide. Panax species produces triterpene saponins called ginsenosides, which are classified into two groups by the skeleton of aglycones, namely dammarane-type and oleanane-type. Dammaranetype ginsenosides dominate over oleanane-type not only in amount but also in structural varieties. Researches shows that the saponins content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In the present study, we isolated and regulated a (Kim et al, 2014;Park et al, 2016;Rahimi et al, 2015;Wang et al, 2014b;Zhao et al, 2015). Moreover, RNAi has been used for the identification or validation of biological function of the targeted transcripts of individual genes in planta (Han et al, 2010;Sun et al, 2013). Many reports indicated the possibility of altering ginsenoside levels by regulating genes encoding enzymes involved in ginsenoside biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, we isolated and regulated a (Kim et al, 2014;Park et al, 2016;Rahimi et al, 2015;Wang et al, 2014b;Zhao et al, 2015). Moreover, RNAi has been used for the identification or validation of biological function of the targeted transcripts of individual genes in planta (Han et al, 2010;Sun et al, 2013). Many reports indicated the possibility of altering ginsenoside levels by regulating genes encoding enzymes involved in ginsenoside biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has reported that inhibiting the expression of protopanaxadiol synthase can depress the levels of protopanaxadiol and protopanaxatriol. Moreover, they also suggested that the P450 synthase content in P. quinquefolius is exceeded than that in P. ginseng (Sun et al, 2013). The RNAi-mediated inhibition of β-Amyrin synthase decreased levels of oleanane-type ginsenoside Ro and increased the level of total ginsenosides in P. ginseng (Zhao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations